1995
DOI: 10.1007/bf00665786
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of estrone and estradiol in hormone-dependent and hormone-independent human breast cancer cells

Abstract: Using different hormone-dependent (MCF-7, T-47D) and hormone-independent (MDA-MB-231, Hs-578S, MDA-MB-436) human breast cancer cells, the interconversion estrone (E1)<-->estradiol (E2) was explored. The data show very clearly that in the hormone-dependent cells the tendency is to form E2 after incubation with E1, whereas after incubation with E2 most of this estrogen remains unchanged. In the hormone-independent cells, in contrast most of E1 remains E1, while E2 is converted into E1. The tendency of the reduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 32 publications
2
20
0
Order By: Relevance
“…Progestins have been shown to inhibit the reductive 17␤-HSD activity as well as to stimulate the oxidative 17␤-HSD activity, respectively in BC cell lines. In contrast, sulfotransferase activity was shown to be increased in MCF-7 and T-47D cell lines when progestins were added [32,41,60,61]. A recent study in BC cells demonstrated different effects on various enzymes depending on what type of progestin and estradiol was combined with [44].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Progestins have been shown to inhibit the reductive 17␤-HSD activity as well as to stimulate the oxidative 17␤-HSD activity, respectively in BC cell lines. In contrast, sulfotransferase activity was shown to be increased in MCF-7 and T-47D cell lines when progestins were added [32,41,60,61]. A recent study in BC cells demonstrated different effects on various enzymes depending on what type of progestin and estradiol was combined with [44].…”
Section: Discussionmentioning
confidence: 96%
“…Thus, STS seems to play a crucial role in local biosynthesis of estrogens in breast (cancer) tissue. Estradiol and various progestogens have been shown to influence STS in BC cells in vitro [38][39][40][41][42][43][44]. In vitro, the effect of steroids on local estrogen formation in normal and malignant breast cells is rather due to changes in STS activity than in its mRNA and protein levels [45].…”
Section: Introductionmentioning
confidence: 99%
“…as such, modulation of the receptor status may coincide with progression of hormone-dependent tumours to a hormoneindependent status (Abul-Hajj, 1979;McCormick et al, 1982;Prudhomme et al, 1984;Welsch, 1985Welsch, , 1987Mauvais-Jarvis et al, 1986;Siiteri et al, 1986;Ball et al, 1988;Castagnetta et al, 1995;Nguyen et al, 1995). In this context, it is interesting to note that MMEC/mnvc3 cells that express exogenous c-m!yc also exhibit about a 60% decrease in oestrogen receptor content relative to the parental MMEC cells.…”
Section: Discussionmentioning
confidence: 99%
“…HSD17B1 (17b-hydroxysteroid dehydrogenase1) is the most active enzyme to produce E2 [7][8][9][10] and significantly overexpressed in breast cancer, which contributes to the stimulation and development of breast cancer., 11,12 HSD17B2, which converts E2 to E1, is dominant in normal breast. 13 Studies have shown that increased HSD17B1 expression or ratio of HSD17B1 and HSD17B2 expression is associated with poor clinical outcome of estrogen-dependent breast cancer patients. 12,14 Besides HSD17B1, HSD17B7 has been identified as a key enzyme for the viability of breast cancer due to the dual functions on activation and reduction of estrogen and androgen.…”
Section: Introductionmentioning
confidence: 99%